Nutrient composition, in vitro true digestibility (IVTD) and methane production potential of fodder tree leaves - RAMACHANDRAN, M; BHARATHIDHASAN, A; BALAKRISHNAN, V (The Indian Journal of Animal Sciences, 2015)
This work was carried out to estimate the nutrient composition and methane production potential of various tree leaves to develop a database on methane production. Highest organic matter (OM) content was recorded in cashew leaves (96.87%) and lowest value was recorded in mulberry leaves (86.03%). Ether extract (EE) content of various tree leaves ranged from 0.54 to 8.74%. Neutral detergent fibre (NDF) was highest in velvel leaves (65.03%) and lowest in Murungai leaves (19.48%). Lowest in vitro true digestibility was observed in velvel leaves (41.59%) and highest value was observed in maramalli leaves (75.59%). Mulberry leaves had lowest methane production potential at half life (t1/2) (0.21 ml/100 mg truly digested substrate) and highest methane production potential at half life (t1/2) was recorded in velvel leaves (1.98 ml/100 mg truly digested substrate). Agathi leaves had highest (P<0.05) methane production potential at 24 h (2.72 ml/100 mg truly digested substrate) compared to all other tree leaves. It can be concluded that average OM, EE and NDF content of various tree leaves was 90.83, 4.67 and 40.53%, respectively. Average methane production potential of different tree leaves at half life and 24 h was 0.93 and 1.55 ml /100 mg truly digested substrate, respectively.